2017
DOI: 10.1111/avj.12561
|View full text |Cite
|
Sign up to set email alerts
|

Neospora caninum in beef herds in New South Wales, Australia. 1: seroprevalence study

Abstract: Overall, about two-thirds of all herds in NSW showed evidence of infection, but the seroprevalence of N. caninum in individual beef cattle in NSW was low to moderate (1.8-11.3%). Significant differences occurred between regions. The risk for herds being positive for N. caninum was associated with geographic factors, particularly in the Mid-North Coast Region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…From this population, a request to participate was sent to a random sample of 1780 properties stratified by geographic region. Of them, 63 properties were successfully recruited and approximately 55 cattle from each herd were bled and tested using the N. caninum ELISA for the seroprevalence study …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From this population, a request to participate was sent to a random sample of 1780 properties stratified by geographic region. Of them, 63 properties were successfully recruited and approximately 55 cattle from each herd were bled and tested using the N. caninum ELISA for the seroprevalence study …”
Section: Methodsmentioning
confidence: 99%
“…The full questionnaire included property attributes, detailed reproductive information and herd management factors, including other enterprises on the farm, and questions about canid exposure. Where possible, respondents were asked to include information about the outcome of pregnancy for the animals that were tested as part of the N. caninum seroprevalence study …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first of the production animal articles in this issue describes the distribution of Neosporum caninum in NSW beef cattle . It was done through strategic sampling of beef breeding cows across the state and serological testing using ELISA.…”
mentioning
confidence: 99%
“…The first of the production animal articles in this issue describes the distribution of Neosporum caninum in NSW beef cattle. 4 It was done through strategic sampling of beef breeding cows across the state and serological testing using ELISA. This disease costs the Australian beef industry an estimated A$25 million per year; studies reported more than 10 years ago showed individual prevalences in Queensland and NSW ranging from 10% to 24%, with between 35% and 99% of herds having at least one positive result.…”
mentioning
confidence: 99%